«I am black, nice color»: The role of «race» in the identity of Africandescendants in Peru - Valdivia Vargas, Néstor (2014)
This document is based on a recent study on the relation between ethnicity, culture, «race» and ancestry among Afro-Peruvians. Findings show that while construction of the «black» or Afrodescendant identity in Peru holds the cultural dimension as a central component, it mainly - and fundamentally- revolves around the idea of the existence of a «black race». According to these «racialized» identity criteria, the boundaries of an Afro-descendant «we» cover only those with certain phenotypic markers that Afro-Peruvians themselves consider as defining membership in the «black race». The phenotypical «evidence» of «blackness» thus appears as a kind of «necessary condition» for the «black»/Afro- Peruvian identity. This form of self-identification poses a threat to the political discourses and projects of Afro-Peruvian organizations seeking to build a «de-racialized» Afrodescendant identity, one that is linked to a historical memory of the African diaspora which, nonetheless, seems to hold a weak presence among our country’s people of African descent.